Optimal endoscopic drainage strategy for unresectable malignant hilar biliary obstruction - Itaru Naitoh; Tadahisa Inoue (Korean Society of Gastrointestinal Endoscopy, 2023)
Endoscopic biliary drainage strategies for managing unresectable malignant hilar biliary obstruction differ in terms of stent type, drainage area, and deployment method. However, the optimal endoscopic drainage strategy remains unclear. Uncovered self-expandable metal stents (SEMS) are the preferred type because of their higher functional success rate, longer time to recurrent biliary obstruction (RBO), and fewer cases of reintervention than plastic stents (PS). Other PS subtypes and covered SEMS, which feature a longer time to RBO than PS, can be removed during reintervention for RBO. Bilateral SEMS placement is associated with a longer time to RBO and a longer survival time than unilateral SEMS placement. Unilateral drainage is acceptable if a drainage volume of greater than 50% of the total liver volume can be achieved. In terms of deployment method, no differences were observed in clinical outcomes between side-by-side (SBS) and stent-in-stent deployment. Simultaneous SBS boasts a shorter procedure time and higher technical success rate than sequential SBS. This review of previous studies aimed to clarify the optimal endoscopic biliary drainage strategy for unresectable malignant hilar biliary obstruction.